An Observational Study of Stromal CD10 Expression in Breast Carcinoma and Its Association with Clinicopathological Parameters at SMS Medical College and Hospital - Sharma, Ankita Kumari; Hemrajani, Deepika; Harsh, Anita; Pancharia, Aruna; Yadav, Monika (Asian Pacific Journal of Cancer Biology, 2024)
Introduction: Female breast cancer is now more prevalent than lung cancer worldwide, with an estimated 2.3 million new cases worldwide, or 11.7% of all cancer cases. Breast cancer is an epithelial malignancy, but tumor microenvironment i.e. stroma plays remarkable role in invasion and metastasis. The cross talk between tumor cells and stromal cells is critical step in tumor progression as a result there is increased interest in developing novel therapies targeting the microenvironment. Aim and Objectives: To study the frequency and intensity of stromal CD10 expression in invasive breast cancer and to correlate it with various clinicopathological parameters. Materials and Methods: The study was conducted in Department of Pathology at S.M.S. Medical College, Jaipur. CD 10 expression in 70 patients diagnosed with carcinoma breast during the period of 2021-2022, assessed by immunohistochemistry and scored as negative (<10% stromal positivity), weak (10-30% stromal positivity) and strong (>30% stromal positivity) and statistically analyzed with other parameters. Results and Discussion: Out of the 70 cases, 51 (72.86%) showed CD10 positivity in the stroma, with 28 (40%) showing strongly positive and 23 (32.86%) with weakly positive results. With respect to histopathological grade (P value = 0.0234), molecular subtype (P value = 0.0006), and PR negativity (P value = 0.0480), CD10 expression in the stroma showed a positive correlation. Conclusion: The correlation between stromal expression of CD10 and histopathological grade, molecular subtype, and PR negativity was statistically significant. To confirm CD10 expression in invasive breast cancer as a predictor of overall survival rates and disease-free survival, more research is required..